Nonlinear evolution of the acoustic wave in a semi-ideal gas - PERELOMOVA, A.; LEBLE, S.; KUŚMIREK-OCHRYMIUK, M. (Archives of Acoustics, 2001)
The method of deriving the evolution equation, based on projecting is applied for the evaluation of the sound velocity and the parameters of nonlinearity for real gases and liquids. The method yields in a coupled system of interacting modes: leftwards and rightwards acoustic and heat modes in the one-dimensional flow problem. The general form of the caloric equation of state allows to get the coefficients of nonlinear equations in the general form. As an example, the sound velocity and the nonlinear parameter B/A for a variety of semi-ideal gases were calculated and the results compared with experimental data.